The Effect of Financial Performance on Going Concern Audit Opinion on Consumer Non-Cyclical Companies Listed on the Indonesia Stock Exchange for the 2021-2023 Period - Tertia, Janice Clairine; Sunaryo, Tarko (Eduvest - Journal of Universal Studies, 2025)
The purpose of this research is to determine the effect of financial performance, as measured using the financial ratios of profitability, liquidity, solvency and activity ratios, on audit opinions with the assumption of going concern in companies engaged in the non-cyclical consumer industry sector listed on the Indonesia Stock Exchange in 2021 to 2023. The financial ratios used to assess financial performance include return-on-asset, return-on-equity, gross profit margin, net profit margin, current ratio, quick ratio, cash ratio, debt-to-equity, debt-to asset, total asset turnover, fixed asset turnover, and inventory turnover. This research applies a quantitative method using secondary data as a source of research data. The sample was selected by applying the purposive sampling method to a population that met the previously determined requirements. The number of samples selected was 264 samples from 88 non-cyclical consumer companies. The regression model used is logistic regression analysis regarding the dependent variable studied is dichotomous. Then, data management is carried out using the SPSS (Statistical Product and Service Solutions) version 26 statistical program. Based on the results of this research, it can be seen that financial performance proxied by the cash ratio and debt-to-asset ratio only has an impact on the provision of going concern audit opinions on a company.